2014
DOI: 10.3201/eid2008.140596
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against MERS Coronavirus in Dromedary Camels, Kenya, 1992–2013

Abstract: Dromedary camels are a putative source for human infections with Middle East respiratory syndrome coronavirus. We showed that camels sampled in different regions in Kenya during 1992–2013 have antibodies against this virus. High densities of camel populations correlated with increased seropositivity and might be a factor in predicting long-term virus maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
224
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(246 citation statements)
references
References 14 publications
16
224
2
4
Order By: Relevance
“…The detection of MERS-CoV in dromedary camels imported from Sudan and Ethiopia for slaughter in Egypt [9], as well as serological evidence of previous MERS-CoV infection in dromedaries in Ethiopia, Kenya [13], Nigeria [14], Tunisia [14] and the Canary Islands (Spain; some originating from Morocco) [5] suggests that the virus could be geographically widespread in the dromedary camel populations on the African continent and that previously undetected transmission to humans may occur outside of the Arabian Peninsula [14].…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…The detection of MERS-CoV in dromedary camels imported from Sudan and Ethiopia for slaughter in Egypt [9], as well as serological evidence of previous MERS-CoV infection in dromedaries in Ethiopia, Kenya [13], Nigeria [14], Tunisia [14] and the Canary Islands (Spain; some originating from Morocco) [5] suggests that the virus could be geographically widespread in the dromedary camel populations on the African continent and that previously undetected transmission to humans may occur outside of the Arabian Peninsula [14].…”
Section: Zoonotic Transmissionmentioning
confidence: 99%
“…From studies in Kenya and Saudi Arabia, MERS-CoV has been circulating in dromedary camels for at least 20 years, and young dromedary camels have lower seroprevalences and are more likely to carry infectious virus. 63 Swabs from milking camels and milk from two locations in Qatar tested positive for MERSCoV RNA using real-time RT-PCR testing. Analysis of an outbreak of MERS-CoV infection in humans associated with a barn in Qatar in October 2013 found dromedaries and humans were infected with nearly identical strains of MERSCoV.…”
Section: Middle East Respiratory Syndrome Coronavirusmentioning
confidence: 99%
“…Further, many camels in Saudi Arabia are imported from East Africa; additional studies showed that sera positive for MERS-CoV were detected in camels in East, West and North Africa from as early as 1992 59 , 60 ., 61 indicating widespread circulation of MERS-CoV in camel populations for many years.…”
Section: Epidemiology Animal Sourcementioning
confidence: 99%